Estimation of extreme rainfall over north India (MAUSAM, 1971)
Hershfield (1961) using statistical techniques worked out PMP estimates for USA which have been found to be comparable with the results obtained by the conventional storm analysis methods. This technique has been utilised in this paper for the preparation of generalised charts of PMP for the plain areas of different States in north India. A table showing PMP values for individual station in the Himalayan region has also been prepared. In addition to the above, an attempt has also been made to draw an envelope frequency factor curve based upon the rainfall data of 760 long-period stations in north India. This curve has been compared with the similar curve prepared by Hershfield on the basis of world record rainfall data.